Proceedings of the 2015 Annual Symposium on Computer-Human Interaction in Play 2015
DOI: 10.1145/2793107.2810312
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding the Importance of Co-Located Gameplay

Abstract: Analyzing the social context present in a gameplay environment and its effect on player experience can provide insights informing the design and social value of games. We investigate the influence of social condition (cooperative or competitive play with a human player versus computer-controlled character) on player experience. The study controlled for co-presence by ensuring that another individual attending to the same stimulus was present in all conditions. Although physiological measures were not significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Multiplayer games have been chosen, since they have been less explored in HRI studies. Research has shown that players react differently when playing with other human players as compared to artificial agents [74], and the overall multiplayer gaming experience produced higher pleasure and perceived arousal [91], as well as more fun and less boring experiences in players [47].…”
Section: Introductionmentioning
confidence: 99%
“…Multiplayer games have been chosen, since they have been less explored in HRI studies. Research has shown that players react differently when playing with other human players as compared to artificial agents [74], and the overall multiplayer gaming experience produced higher pleasure and perceived arousal [91], as well as more fun and less boring experiences in players [47].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the overall popularity of game streaming, the motives and experiences of spectators have been of ongoing interest to the games user research community [21,43,50]. Instead of just focusing on the experience of the active player, a variety of work has broadened the research scope by explicitly investigating the spectator experience [4,11,13,28,44] and the motivations for viewers to spend their free time watching others play [10,18,24].…”
Section: Related Workmentioning
confidence: 99%
“…Research on co-location in games validates that players respond di erently when playing with or against other human players, compared with singleplayer experiences or play against an arti cial agent. For example, Wehbe and Nacke [31] investigate the e ect of co-location on players, nding that players demonstrated higher pleasure and perceived arousal in co-located multiplayer conditions than singleplayer conditions. Similarly, Mandryk and Inkpen [18] report that players found co-located multiplayer play with a friend more engaging (i.e., more fun, less frustrating, less boring) than the same (singleplayer) experience against an arti cial opponent.…”
Section: Singleplayer and Multiplayermentioning
confidence: 99%
“…Whether these results hold true for networked play is unknown, though we can speculate given that singleplayer Gwario is functionally similar to a naïve, networked implementation, as both omit any means of direct communication between players (and traditionally, networked HCGs do not permit direct player communication). Similarly to other studies of co-location [18,31], our study was conducted in a lab environment. While we took steps to mitigate the encumbrances of a lab environment and provide a non-intrusive, comfortable space for play, we acknowledge this may not have been the most natural space for gameplay.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation